(untitled) (International Journal of Environmental Sciences, 2025)
The economic prosperity of a nation is closely linked to the well-being of it’s industries. This study seeks to examine the historical evolution of industries in Tamil Nadu across various periods. It explores the significance of major ports and trading activities in ancient Tamil regions and their contributions to industrial development. The study further analyzes the social factors that played a pivotal role during the medieval era, including the privileges accorded to craftsmen and the prevailing regulatory frameworks of the time. Additionally, it discusses the role of the British in systematizing taxation and implementing administrative reforms in the industrial sector. The paper concludes with an analysis of the establishment of the Indian Industrial Commission in 1916 and its implications.